Prodrugs of Antiinfective Agents: A Review - Mona Piplani; Avtar Chand Rana; Prabodh Chander Sharma (Frontiers Media S.A., 2016)
Prodrugs are the pharmacologically inactive derivatives of active drugs typically intended to optimize the exposure of active drug at target site, through manipulation of its physicochemical, biopharmaceutical or pharmacokinetic properties. This approach has a number of advantages over conventional drug administration. Antiinfective agents are associated with number of limitations, responsible for their reduced bioavailability. Various antiinfective prodrugs have been synthesized with reduced side effects and improved pharmacological properties. The present paper illustrates different vistas of prodrug approach of antiinfective agents describing brief classification, synthetic approaches, pharmacological aspects and recent patents. It is a very productive area of research and its prologue in human therapy has given triumphant outcomes in improving the clinical and therapeutic effectiveness of drugs. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.